2020
DOI: 10.1039/d0nr05774f
|View full text |Cite
|
Sign up to set email alerts
|

Role of defects in carbon materials during metal-free formic acid dehydrogenation

Abstract: Commercial graphite (GP), graphite oxide (GO), and two carbon nanofibers (CNF-PR24-PS and CNF-PR24-LHT) were used as catalysts for the metal-free dehydrogenation reaction of formic acid (FA) in liquid phase. Raman...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 74 publications
1
18
0
Order By: Relevance
“…Carbon monoxide prefers bonding on the metal atoms rather than at the interface between the cluster and the support. This may be attributed to the interaction of the O‐lone pair electrons with the inactive π‐conjugation of the support [41] . Then, formic acid was brought and relaxed on the most favourable CO adsorption site with diverse orientations.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon monoxide prefers bonding on the metal atoms rather than at the interface between the cluster and the support. This may be attributed to the interaction of the O‐lone pair electrons with the inactive π‐conjugation of the support [41] . Then, formic acid was brought and relaxed on the most favourable CO adsorption site with diverse orientations.…”
Section: Resultsmentioning
confidence: 99%
“…61,62 Combining experimental and DFT studies, we reported recently the promising activity and selectivity of metal-free carbon catalysts in the generation of H 2 from formic acid. 63 In particular, we demonstrated that defects, especially single vacancies, are active in the formic acid dehydrogenation reaction even in the presence of oxygen groups. Similar investigations including a wide range of carbon dopants proved the same results in ammonia reforming.…”
Section: Introductionmentioning
confidence: 82%
“…All carbon-based materials were modelled starting from a single layer slab of a 6 Â 6 pristine graphene supercell and introduced different defects: single vacancy (SV), double vacancy (DV) and three different Stone Wales defects (SW1, SW2, and SW3). 63 The supercell is in a hexagonal crystalline system with unit cell vectors a and b lying in the surface plane and perpendicular to the c axis. Both, a and b, were optimized at 14.8 Å, in good agreement with experimental values obtained by Transmission Electron Aberration-corrected Microscopy (TEAM).…”
Section: Methodsmentioning
confidence: 99%
“…The decomposition of formic acid can take place via two possible pathways dependent upon the catalyst, reaction temperature, and reactant concentrations. The dehydrogenation of formic acid is shown in Equation (1), and the dehydration reaction is shown by Equation (2). The former reaction is slightly exothermic, while the latter reaction is slightly endothermic.…”
Section: Modelling Methodologymentioning
confidence: 99%
“…Formic acid (HCOOH) has proven immensely popular as a favourable hydrogen storage/generation material due to its high gravimetric and volumetric hydrogen capacity, ease of handling, non-toxicity, stability at room temperature, and abundant supply from the conversion of biomass and carbon dioxide (CO 2 ) [1]. The decomposition of formic acid reaction can be conducted in a liquid phase (at temperatures lower than 373 K) as well as in a gas phase (at excess temperatures), resulting in the dehydrogenation or dehydration pathways [2]. The former produces CO 2 and hydrogen (H 2 ) as products, and the latter generates carbon monoxide (CO) and water (H 2 O) products.…”
Section: Introductionmentioning
confidence: 99%